Pengaruh Kebijakan Keselamatan dan Kesehatan Kerja (K3) TerhadapKeselamatan Kerja dan Efisiensi Proses Ekspor Logam Timah di PT.Timah Tbk Muntok, Bangka Barat - arslan masroor hamidullahh; Evyana Diah Kusumawati; Agus Pamungkas Rismilia Putra (Politeknik bumi Akpelni, 2025)
This study aims to analyze the effect of Occupational Health and Safety (OHS) policies onworkplace safety and the efficiency of tin metal export processes at PT. Timah Tbk. The researchemployed a quantitative method, with data collected through questionnaires distributed to 40employees of PT. Timah Tbk. Based on the T-test results, the relationship between variable X andY1 yielded a t-value of 20.365 > t-table value of 2.024 and a significance value of 0.001 < 0.05,indicating that OHS policies (X) significantly influence workplace safety (Y1). Thus, Ho1 isrejected, and Ha1 is accepted. OHS policies positively and significantly impact workplace safety,leading to the rejection of Ho2 and acceptance of Ha2. Additionally, the T-test results for variableX and Y2 yielded a t-value of 23.176 > t-table value of 2.024 and a significance value of 0.001 <0.05, indicating that OHS policies (X) significantly influence the efficiency of the export process(Y2). Consequently, Ho2 is rejected, and Ha2 is accepted. The independent variable contributes91% to workplace safety and 93% to the efficiency of tin metal export processes at PT. Timah Tbk.